Whole transcriptome sequencing reveals HOXD11-AGAP3, a novel fusion transcript in the Indian acute leukemia cohort - Desai, Sagar Sanjiv; Ravindran, Febina; Panchal, Amey; Ojha, Nishit; Jadhav, Sachin; Choudhary, Bibha (Frontiers in Genetics, 2023)
Acute leukemia is a heterogeneous disease with distinct genotypes and complex karyotypes leading to abnormal proliferation of hematopoietic cells. According to GLOBOCAN reports, Asia accounts for 48.6% of leukemia cases, and India reports ~10.2% of all leukemia cases worldwide. Previous studies have shown that the genetic landscape of AML in India is significantly different from that in the western population by WES. In the present study we have sequenced and analyzed 9 acute myeloid leukemia (AML) transcriptome samples . We performed fusion detection in all the samples and found a novel fusion HOXD11-AGAP3 in 3 patients, BCR-ABL1 in 4, and KMT2A-MLLT3 in one patient. On categorizing the patients based on their cytogenetic abnormalities and performing a differential expression analysis, followed by WGCNA analysis, we observed that in the HOXD11_AGAP3 group, correlated co-expression modules were enriched with genes from pathways like Neutrophil degranulation, Innate Immune system, ECM degradation, and GTP hydrolysis. Immune profiling using CIBRSORTx revealed differences in the immune profiles across all the samples. The findings highlight population-specific Acute Leukemia transcriptome signatures and the presence of a novel fusion involved in leukemogenesis in an Immune system-dependent manner.